2019
DOI: 10.3233/jad-180427
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Prevalence of Polypharmacy in People with and without Dementia from 2000 to 2014: A Nationwide Study

Abstract: Background: Early and accurate diagnosis of dementia opens the door to appropriate treatment, support, and counseling. Despite availability of evidence-based guidelines for diagnostic evaluation of dementia, the diagnostic rate in people with dementia is low and the quality of dementia diagnoses is unknown. Objective:The overall aim of this register-based study was to analyze the quality of diagnostic evaluation of dementia by assessing nationwide geographical variations in a range of indicators. Methods:A reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…There are also notable sex differences in the prevalence of individual and cooccurring medication classes and chronic conditions [7,19] and potentially harmful drug-drug interactions [12]. Though recent studies have explored broad trends in multimorbidity [2,4,5] and/or polypharmacy [12,19,20,28], few have examined sex-and age-specific trends in both [20] among older adults or investigated variation over time in the impact of multimorbidity and age on medication use [29][30][31][32], particularly among older men and women.…”
Section: Introductionmentioning
confidence: 99%
“…There are also notable sex differences in the prevalence of individual and cooccurring medication classes and chronic conditions [7,19] and potentially harmful drug-drug interactions [12]. Though recent studies have explored broad trends in multimorbidity [2,4,5] and/or polypharmacy [12,19,20,28], few have examined sex-and age-specific trends in both [20] among older adults or investigated variation over time in the impact of multimorbidity and age on medication use [29][30][31][32], particularly among older men and women.…”
Section: Introductionmentioning
confidence: 99%
“…Polypharmacy is increasing in older adults, in Australia and internationally, 1,2 and is associated with adverse outcomes including falls, functional decline, hospitalisation and death 3,4 . Use of medications with anticholinergic and sedative properties is of concern because they have cumulative effects on functional impairment in older adults 5 .…”
Section: Introductionmentioning
confidence: 99%
“…A prevalence of 21.1% for polypharmacy in BASE-II in an analysis including people younger than 65 years at baseline assessment was reported before [20]. Studies involving community-dwelling adults have shown even higher prevalences of 36.1 to 39.1% (polypharmacy) and 7.7 to 8.9% (excessive polypharmacy) [44, 45]. A large Dutch study described an increase in polypharmacy over time from 1999 to 2014 [46].…”
Section: Discussionmentioning
confidence: 85%
“…A large Dutch study described an increase in polypharmacy over time from 1999 to 2014 [46]. Another Danish study described increasing polypharmacy from 2000 to 2011 but a stable prevalence from 2011 to 2014 [45]. Living longer typically results in the manifestation of chronic disease.…”
Section: Discussionmentioning
confidence: 99%